Fusões, aquisições estratégicas, e capacidades tecnológicas inovadoras: evidências da indústria de telecomunicações multinacional - Galindo, Weidson Torres (2008)
This dissertation studies the innovative technological capabilities available in the merger and acquisitions processes and the relationship between these processes with the technological capabilities accumulation to get convergence of technology and services. This study was examined in fourteen companies of the telecommunications industry during 2002 to 2007. Starting on 1990 there were from one end a profusion of studies on the technological capabilities as source of competitive advantages; from another end there are studies on merger and acquisitions with the objective to evaluate the motivations derived from technological factors and stimulation to the competition and the opening of the market. However few of the empirical studies of long stated period that examine the correlation of these events in the industry of telecommunications under the optics of the technological qualification in the level of the companies and for the strategic perspective of enterprise based on the dynamics abilities. An analytical framework already available in the literature was used to describe the contribution of the merger and acquisitions processes for the accumulation of innovative technological capabilities in the studied companies. However the framework was adapted specifically for the industry of Telecommunications. This dissertation also studies the importance of the strategic merger and acquisitions as organizational form in the complementation of technological capability for external sources. Such empirical evidences had been collected from information and data bases published for the own companies who had been examined in this dissertation. Regarding the results, it was found that: 1. In terms of participation with ingress technological capabilities in strategic merger and acquisitions the equipment manufacturers had entered with 71% to 55 of the technological capabilities and the service operator company had entered with 61% to 71 technological capabilities. 2. In terms of implications of the merger and acquisitions for the configuration of resultant technologic capabilities, it was found that the equipment manufacturers had increased 31% the ratio of convergence of technology and the operators of services had increased 4% the ratio for the change in the organizational structure. 3. Regarding the accumulation technological capability to obtain convergence of technology and services was verified the increase these technological capabilities after the merger and acquisitions process in the companies studied. Considering the limitation of this study, the evidences found in this dissertation suggest that the companies use the processes of strategic merger and acquisitions to search for external complementation of their knowledge base to compete in the globalization market. The result demonstrates that this movement has implied in an alteration and accumulation of capability from organization on innovative technological activities regarding the convergence of technology and services.